Social Media Marketing and Fast-Food Restaurant Brand Loyalty: The Mediating Role of Brand Gestalt - Wantah, Angela Marcella; Mandagi, Deske W. (Jurnal Informatika Ekonomi Bisnis, 2024)
With the advancement of technology in the present era, it has become an innovation for many companies to leverage these advancements. Social media stands as evidence of technological progress in this era. Social media marketing (SMM) is a means to capture consumer attention towards brand content on social media platforms. SMM also serves to cultivate relationships with loyal customers. This study aims to investigate the impact of social media marketing on brand loyalty in fast-food restaurants in Manado, with brand gestalt playing a mediating role. The research adopts a quantitative methodology, with primary data collected through online questionnaires from 135 fast-food restaurant customers in Manado, North Sulawesi. Convenience sampling is employed for sample selection. The data is then analyzed using Structural Equation Modeling (SEM) utilizing SmartPLS. The findings of this analysis demonstrate that social media marketing significantly influences brand loyalty and brand gestalt. Additionally, a significant and positive relationship is detected between brand gestalt and brand loyalty. This research contributes to a deeper understanding of the role of social media marketing and brand gestalt in shaping consumer loyalty in the fast-food restaurant industry, offering insights that can inform strategic marketing efforts in this sector.